Análise espacial dos acidentes de trânsito em rodovias federais no Estado de Goiás – Brasil - Alex Mota dos Santos; Bernard Silva de Oliveira; Fabrizia Gioppo Nunes (Confins)
Spatial analysis of traffic accidents is fundamental to comprehend and recognize critical points of road sections and hence establish strategies to reduce these occurrences. This study aims to conduct the spatial analysis of the traffic accidents in 2016 at federal highway sections of the state of Goiás, Brazil. The geocoding was performed in a Geographic Information System (GIS) and mapping of the accident data was provided by NURAM/PRF/GO. Kernel’s density estimation method was applied to analyze the spatial variability and was correlated with data of: fleet, number of cars and engine rate. The results revealed that BR-060, specifically between Goiânia and Distrito Federal, and BR-153, which are the areas that not only present the highest density of traffic accidents, but also a high density of the most severe accidents, with cases of death. Despite being under concession and having the best conditions of traffic and inspection by mobile and fixed equipment, these road sections are configured as critical points. Finally, there was no evidence that the fleet, the number of light vehicles or the motorization rate explain the occurrences of accidents in the federal highways of Goiás, in the year analyzed.